2018
DOI: 10.13048/jkm.18037
|View full text |Cite
|
Sign up to set email alerts
|

Anti-osteoarthritic effects of a combination of pomegranate concentrate powder, Eucommiae cortex and Achyranthis radix in rats

Abstract: We examined the effects of a mixed formula consisting of dried pomegranate concentrate powder (PCP) and the aqueous extracts of Eucommiae cortex (EC) and Achyranthis radix (AR) in rats with surgically induced osteoarthritis (OA). Methods: Two weeks after OA-inducing surgery, a PCP:EC:AR 5:4:1 (g/g) combination or single formula was orally administered. Changes in body weight, knee thickness, maximum knee extension angle, bone mineral density of the knee joints, femoral and tibial articular surfaces, and compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…Other studies in surgically-induced OA rats reported that 200 mg/kg BW pomegranate concentrated powder for 58 and 28 days significantly decreased articular cartilage in femoral and tibial areas with synovial membrane prostaglandin E2 (PGE2) levels, 5-lipoxygenase (LPO) function of articular cartilage in femoral and tibial areas with synovial membrane, MMP-2 and MMP-9 activities of femoral and tibial articular cartilage with synovial membrane, and mRNA expression of synovial membrane collagen type-II in comparison with arthritic controls. 29,30 Moreover, considerable elevation was observed in femoral and tibial articular cartilage collagen type-II mRNA expression as well as mRNA expression of Sox-9 and aggrecan in femoral and tibial articular cartilage with synovial membrane in comparison with arthritic control group. 29,30 In another research in surgically-induced OA rabbits, Akhtar et al 31 stated that 34 mg/kg BW pomegranate fruit extract in water for 56 and 70 days significantly decreased expression of MMP-3, MMP-9, and MMP-13 and level of PGE2 in the synovial fluid compared with arthritic control rabbits.…”
Section: Laboratory Findingsmentioning
confidence: 93%
See 1 more Smart Citation
“…Other studies in surgically-induced OA rats reported that 200 mg/kg BW pomegranate concentrated powder for 58 and 28 days significantly decreased articular cartilage in femoral and tibial areas with synovial membrane prostaglandin E2 (PGE2) levels, 5-lipoxygenase (LPO) function of articular cartilage in femoral and tibial areas with synovial membrane, MMP-2 and MMP-9 activities of femoral and tibial articular cartilage with synovial membrane, and mRNA expression of synovial membrane collagen type-II in comparison with arthritic controls. 29,30 Moreover, considerable elevation was observed in femoral and tibial articular cartilage collagen type-II mRNA expression as well as mRNA expression of Sox-9 and aggrecan in femoral and tibial articular cartilage with synovial membrane in comparison with arthritic control group. 29,30 In another research in surgically-induced OA rabbits, Akhtar et al 31 stated that 34 mg/kg BW pomegranate fruit extract in water for 56 and 70 days significantly decreased expression of MMP-3, MMP-9, and MMP-13 and level of PGE2 in the synovial fluid compared with arthritic control rabbits.…”
Section: Laboratory Findingsmentioning
confidence: 93%
“…14 Also, animal 19,20 and human 21,22 researches did not indicate any undesirable outcomes after pomegranate intake. Experimental studies [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] and clinical trials [40][41][42][43][44] investigated the beneficial properties of pomegranate in OA prevention and treatment. Nevertheless, no systematic review exists regarding pomegranate and OA; therefore, in present article, we systematically studied accessible researches regarding pomegranate and OA in human, animal, and in vitro models and likely mechanistic pathways.…”
Section: Introductionmentioning
confidence: 99%
“…The anti-OA effects of PCP:EC:AR were similar to those seen in rat and mouse models of OA; thus, PCP:EC:AR effectively relieves OA symptoms in various animal models. The PCP:EC:AR formula used herein was informed by our previous in vitro [54,64] and in vivo [55,65] experiments on OA rats.…”
Section: Discussionmentioning
confidence: 99%
“…A.Ş., Ankara, Turkey) contained 1.15 mg/g ellagic acid, EC contained 1.58 mg/g pinoresinol diglucoside, and AR contained 0.26 mg/g ecdysterone as active components, respectively (Health Love Ltd., Anyang, Korea). PCP:EC:AR doses of 50, 100, and 200 mg/kg represented the high-, medium-, and low-dose conditions, respectively, as in our previous study on dose-dependent efficacy in a surgically induced OA rat model [55]. The PCP:EC:AR mixed formula (50, 100, and 200 mg/kg) was administered orally (once a day for 56 days, beginning 5 weeks after OA surgery) in a volume of 5 mL/kg distilled water using a gastric tube attached to a 20 mL syringe.…”
Section: Preparation and Administration Of Test Substancesmentioning
confidence: 99%
“…In rats with ACLT OA, the anti-inflammatory and chondrogenic activities of PEA-Mix synergistically enhanced the anti-OA effect of PCP, EC, and AR. 28 However, ACLT OA does not accurately reflect the pathogenesis of OA. MIA causes inflammation and joint destruction, while ACLT directly induces joint destruction and then synovial inflammation; both mimic OA.…”
Section: Discussionmentioning
confidence: 99%